(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Alopecia areata in childhood is an autoimmune condition that causes hair loss in specific areas. Although it is not physically harmful, it can affect children’s self-esteem. Treatment involves topical approaches, such as corticosteroids, with a variable prognosis. Objective: The aim of this article is to briefly and clearly explain the clinical manifestations and therapeutic approach to alopecia areata in children. Materials and Methods: A synthesis of scientific articles and medical literature related to pediatric alopecia was carried out in the PubMed and SciELO databases, using the keywords: Pediatric Alopecia; Clinical Manifestations; Diagnosis and Management and 1390 articles were found. After adding the filter: "since 2019", 641 articles were located. After selecting based on relevant titles, methodology, objectives and results, a compilation of 4 articles was obtained for analysis. Information was collected on the clinical manifestations of this condition, diagnostic and treatment options, as well as approaches to managing alopecia in children. Results: Childhood alopecia can present in various forms, with alopecia areata being the most common, characterized by hair loss in specific areas of the scalp. Symptomatic manifestation is most common in the first decade of life. Diagnosis is clinical, with a medical history and tests if necessary. The regulation of immune cells plays an important role in alopecia areata and its dysfunction can lead to the interruption of the hair growth cycle. In addition, alopecia areata can be associated with other autoimmune diseases and its management may require multidisciplinary approaches. Treatment depends on the cause and extent of hair loss and can include laser therapy, corticosteroids, immunotherapy, hair transplantation, among others. Emotional support for the child and family is also important to deal with the emotional and social impact of alopecia. Conclusion: Diagnosis and proper management are essential to ensure appropriate treatment and minimize the emotional and social impact on affected children. Treatment must be individualized, taking into account the underlying cause, the child’s age and other clinical factors. Psychosocial approaches are key to ensuring the emotional well-being of affected children. It is essential that health professionals specializing in dermatology or paediatrics are involved in the diagnosis and management of paediatric alopecia, with long-term follow-up to monitor the response to treatment and ensure the best possible care for affected children.